Experimental studies of microrods movement in a microfluidic device - John, Oladiran Abiodun (My University, 2011)
The motion of a rod-like particle in a shear flow has been visualize at different flow rates in a microchannel system. The rod-like particles were seen to align along the field lines, but at some intervals, they were observed to tumble. This flipping motion was seen to confirmed the theoretical model by Jeffery [Proc. R. Soc. (1922)(102 161-179)], “that ellipsoids particle suspended in a fluidic system flips occasionally”. Particles released to the fluid in microsystems are subjected to forces exerted by the fluid, and eventually to the certain external forces. Having zero velocity at the walls, the Navier-Stoke equation was used to describe the motion of fluid flow in microchannel. This gives a parabolic nature of the flow profile for the fluid in motion, and it has been described to be solely responsible for the particles movement inside the fluid. The flipping movements of the rod-like particles were studied and the fluctuation in the flipping time and flipping frequency were analyzed. In this thesis, the production of polymer microrods used and the fabrication of the microchannels were discussed in full details. Also the imaging techniques used to visualize movements of the rods in the microfluidics system is described.
Keywords: Fysik; Physical Sciences